1999
DOI: 10.1046/j.1365-2605.1999.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freeze–thawing procedure on chromatin stability, morphological alteration and membrane integrity of human spermatozoa in fertile and subfertile men

Abstract: Cryopreservation is known to impair sperm motility and decrease the fertilization rate by detrimental effects on acrosomal structure and acrosin activity. However, the consequences of cryopreservation on the integrity of the sperm nucleus, chromatin stability and centrosome are less clear. The present study was designed to determine the effect of the freeze-thawing procedure on chromatin condensation (aniline blue staining) and the morphology (strict criteria) and membrane integrity of human spermatozoa. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
92
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 52 publications
9
92
0
1
Order By: Relevance
“…During cryopreservation, the dramatic physical and environmental changes of sperm detrimentally affect the sperm membrane, resulting in a large increase in the percentage of poorly motile sperm or sperm with abnormal morphology [2][3][4]. The negative effects relating to rapid decreases in temperature, such as osmotic injury, cellular dehydration, intra-cellular ice crystal formation, and oxidative stress, also lead to damage to sperm DNA, chromatin instability and DNA denaturation [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During cryopreservation, the dramatic physical and environmental changes of sperm detrimentally affect the sperm membrane, resulting in a large increase in the percentage of poorly motile sperm or sperm with abnormal morphology [2][3][4]. The negative effects relating to rapid decreases in temperature, such as osmotic injury, cellular dehydration, intra-cellular ice crystal formation, and oxidative stress, also lead to damage to sperm DNA, chromatin instability and DNA denaturation [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects relating to rapid decreases in temperature, such as osmotic injury, cellular dehydration, intra-cellular ice crystal formation, and oxidative stress, also lead to damage to sperm DNA, chromatin instability and DNA denaturation [4][5][6][7][8]. Therefore, the reproductive outcome following fertilization with the sperm containing the damaged genetic material may be poor [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the area of clinical ART, the main concern arising from the use of cryopreserved sperm is the reported freezerelated decrease in strict normal morphology and sperm necrosis leading to lower fertilization and IVF/ICSI pregnancy outcome [18]. The results of the present study demonstrated that improvements in strict normal morphology and reduced sperm necrosis could be achieved after zeta potential processing of the cryopreserved-thawed sperm.…”
Section: Discussionmentioning
confidence: 53%
“…The mechanism involved in the zeta selection of sperm with strict normal morphology was based on the greater net negative charge of mature sperm due to membrane sialoglycoproteins [21,22], specifically, gp20-CD52 glycopolypeptides, acquired during transit through the epididymis [23]. Researchers have correlated the maturity of sperm membranes with strict normal morphology, an parameter indicative of successful fertilization [7,24,25]. Disruptions in the sperm maturation process, for example, frequent ejaculations, would result in a less negative-charged sperm due to reduced membrane proteins.…”
Section: Discussionmentioning
confidence: 99%